Reliability of diaphragmatic motor-evoked potentials induced by transcranial magnetic stimulation - Welch, Joseph F. (J Appl Physiol (1985), 2020)
The diaphragmatic motor-evoked potential (MEP) induced by transcranial magnetic stimulation (TMS) permits electrophysiological assessment of the cortico-diaphragmatic pathway. Despite the value of TMS for investigating diaphragm motor integrity in health and disease, reliability of the technique has not been established. The study aim was to determine within- and between-session reproducibility of surface electromyogram recordings of TMS-evoked diaphragm potentials. Fifteen healthy young adults participated (6 females, age = 29 ± 7 yr). Diaphragm activation was determined by gradually increasing the stimulus intensity from 60 to 100% of maximal stimulator output (MSO). A minimum of seven stimulations were performed at each intensity. A second block of stimuli was delivered 30 min later for within-day comparisons, and a third block was performed on a separate day for between-day comparisons. Reliability of diaphragm MEPs was assessed at 100% MSO using intraclass correlation coefficients (ICC) and 95% limits of agreement (LOA). MEP latency (ICC = 0.984, P < 0.001), duration (ICC = 0.958, P < 0.001), amplitude (ICC = 0.950, P < 0.001), and area (ICC = 0.956, P < 0.001) were highly reproducible within-day. Between-day reproducibility was good to excellent for all MEP characteristics (latency ICC = 0.953, P < 0.001; duration ICC = 0.879, P = 0.002; amplitude ICC = 0.789, P = 0.019; area ICC = 0.815, P = 0.012). Data revealed less precision between-day versus within-day, as evidenced by wider LOA for all MEP characteristics. Large within- and between-subject variability in MEP amplitude and area was observed. In conclusion, TMS is a reliable means of inducing diaphragm potentials in most healthy individuals. NEW & NOTEWORTHY Transcranial magnetic stimulation (TMS) is a noninvasive technique to assess neural impulse conduction along the cortico-diaphragmatic pathway. The reliability of diaphragm motor-evoked potentials (MEP) induced by TMS is unknown. Notwithstanding large variability in MEP amplitude, we found good-to-excellent reproducibility of all MEP characteristics (latency, duration, amplitude, and area) both within- and between-day in healthy adult men and women. Our findings support the use of TMS and surface EMG to assess diaphragm activation in humans.